THE INVESTOR’S INVESTMENT DECISIONS ON INDONESIAN MUTUAL FUNDS DURING COVID-19 PANDEMIC - Poan, Roy; Pratama, Hansen; Setyo Santoso, Adhi (Lentera Jurnal Manajemen, 2024)
Purpose – The purpose of this paper is to focus on the role of risk tolerance as the mediator of accounting information, advocate recommendation, and financial knowledge towards investment decisions on Indonesia mutual funds during Covid-19 pandemic. Design/methodology/approach – This study uses quantitative method with primary data. A 28 items instrument was distribute to various social media such as Telegram, Instagram, Line, and Whatsapp by Google Form. The independent variables were accounting information, advocate recommendation, and financial knowledge. The dependent variables were risk tolerance and investment decisions . This research gathers 338 respondents. Finally, the data analysis use PLS-SEM in the SmartPLS 3.0 application to examine the purpose of this paper. Findings – Risk tolerance does not mediate independent variables (accounting information, advocate recommendation, and financial knowledge) towards investment decisions on Indonesia mutual funds during Covid-19 pandemic. However, Investment decisions is being directly influenced by Financial Knowledge, Risk Tolerance, Accounting Information and Advocate Recommendation. Originality/value – Author believes that this is the first study, which applies accounting information, advocate recommendation toward investment decisions with risk tolerance as the mediator on Indonesia mutual funds during Covid-19 pandemic. Keywords – Accounting Information, Advocate Recommendation, Financial Knowledge, Risk Tolerance, Investment decisions Research Type – Research Paper